Smartphone untuk Sistem Katalog Perpustakaan di Era Internet of Things - Djaja Amanda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Smartphone sensors have the potential to revolutionize library catalog systems in the Internet of Things (IoT) era. With the increasing use of Smartphones, libraries can take advantage of various sensors on Smartphone devices to increase the efficiency of the catalog system. One possible application is the use of library locations to assist users in finding library locations. Users can use Smartphones to locate the library, and the library catalog system can use the smartphone's built-in sensors to provide clues to the whereabouts of books. The Global Position System sensor that is used can locate the whereabouts of the library and make a trip mapping from home to the library. It can also be used to track the popularity of certain items and help the librarian decide where to place the book. Smartphone sensors can also be used to increase security in libraries. Overall, the integration of Smartphone sensors into the library catalog system has the potential to improve user services and improve library operational efficiency. The library application system is developed using visual programming using kodular and mysql. As the Internet of Things continues to grow, it is possible for many libraries to adopt Internet of Things technology to improve services.